Efektifitas Kemasan dan Suhu Ruang Simpan terhadap Daya Simpan Benih Kedelai (Glycine max (L.) Meirril) - Purwanti, Marlinda Dwi (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2015)
This study aims to determine the best of packaging types and storage temperature for soybean seeds. The research was conducted in laboratory using a 5x3 factorial design arranged in a completely randomized design (CRD). The first factor was the types of packaging namely PP plastic (Poly Prophylene) vaccuum, PP plastic (Poly Prophylene) without vaccuum, PE plastic (Poly Ethylene) vaccuum, PE plastic (Poly Ethylene) without vaccuum, and control (without packaging). The second factor was the temperature of storage room, i.e. room temperature (27-29 0C), air conditioned room (17-19 0C) and Cooler room (7 0C). Each treatment was replicated 4 times. The results showed that the best packaging type for storing seed at temperature (27-29 0C) PP plastic & PE plastic with and without vaccuum. However, the soybean seed storaged in air-conditioned room (17-19 0C) and Cooler room temperature (7 0C) using the vaccuum, non vaccuum, and withot packaging could maintain the quality of soybead seed for 4 months.